The International Association for the Evaluation of Educational Achievement - Loxley, Bill.; ERIC Clearinghouse on Assessment and Evaluation; American Institutes for Research, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
This digest examines the organization of and international studies conducted by the International Association for the Evaluation of Educational Achievement (IEA). The IEA is a non-profit, private association that conducts international comparative studies on schools and aids the research community in developing international tests and statistical techniques. The IEA has 39 member countries. Policy makers and educators use IEA data to assess alternative curricula, monitor the quality of schooling worldwide, identify effective schools and determine ways of improving their own educational systems, and improve their understanding of the instructional learning process. The organizational structure of IEA consists of a chairperson, general assembly, six-member standing committee, and secretariat. Specific studies are managed by specially appointed steering committees and implemented by national centers. IEA studies include a decennial assessment of a core of school studies in math, science, reading literacy, composition, and foreign languages. Other studies include: a 35-country reading literacy study; the third international mathematics and science study; school and teacher resource assessments that focus on opportunity-to-learn indicators; longitudinal and in-depth case studies; a 21-country computer education study; and a 13-country study of pre-primary early childhood care and education. In the area of information dissemination, the IEA publishes bulletins, a semiannual newsletter, and a guidebook on the IEA research network; the IEA also sponsors conferences on issue-related topics. A 4-item list of additional reading materials is included. (TJH)
Sponsoring Agency: Office of Educational Research and Improvement (ED), Washington, DC.
Contract Number: RI88062003.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agency Role; Educational Assessment; Educational Policy; Educational Research; Elementary Secondary Education; Information Dissemination; International Organizations; International Studies; Organizational Objectives; Private Agencies; Research Projects; Statistical Analysis; Test Construction; International Assn Evaluation Educ Achievement; ERIC Digests; ERIC Publications; ERIC Digests in Full Text